Mechanical characterization and numerical modeling on the yield and fracture behaviors of polymethacrylimide (PMI) foam materials. (15th March 2022) - Huo, Xintao; Jiang, Zhongcheng; Luo, Quantian; Li, Qing; Sun, Guangyong
Highlights: Identification of yield surface for PMI foams under complex loads. Identification of mixed-mode fracture for PMI foams by DIC technique. Effect of density on mechanical performance of PMI foams. Homogenized FE model for fracture of PMI foams. Abstract: Polymethacrylimide (PMI) foam materials exhibit great potential in engineering applications due to their lightweight property. Nevertheless, there is lack of constitutive data regarding the PMI foam materials under complex loading conditions; therefore, this paper reports the systematic experimental characterization of the elastic, plastic and fracture properties of PMI foam materials. In this study, the quasi-biaxial stress loading conditions were generated by the Arcan fixture. A 2D digital image correlation (DIC) system was employed to identify the macroscopic deformation in the tests. Based upon the experimental data, a yield surface of the PMI foam material was calibrated and analyzed, in which both low and high densities of PMI foams were taken into account. It was found that the plastic and fracture parameters can be greatly affected by the foam density owing to different microstructure characteristics. Further, fracture behaviors of the PMI foam were experimentally investigated in the context of linear elastic fracture mechanics (LEFM). The critical energy release rates (ERRs) were extracted for the mixed mode I/II by using cracked specimens subjected to combined tension-shear loadings. A homogenized finite element model was developed for the PMI foam materials and validated with the experiment. This study is expected to gain systematic understanding of PMI foam material properties and provide an effective constitutive model for practical applications of PMI foam materials. Graphical abstract: Image, graphical abstract